Combustion performance of the premixed and diffusion burners with used lubricating oil and used cooking oil as fuel - Masjudin; Chang, Wei-Chin (Modern physics letters. B, Condensed matter physics, statistical physics, applied physics, 2019)
This work investigated combustion performance of the premixed and diffusion burners by measuring flame temperature and gas emissions with used lubricating oil (ULO) and used cooking oil (UCO). Air–fuel ratio (AFR) is an important parameter to investigate combustion performance. Flame temperatures and gas emissions of the burners were examined to know the combustion behavior. The results found were that the flame temperatures in the premixed burner were higher than the diffusion burner at all the AFRs. The maximum flame temperature was obtained at AFR = 16 at all types of burners and fuel blending ratios. The highest flame temperature was 1 3 4 0 ∘ C , which occurred when using 100% ULO with premixed burner at AFR = 16. By adding UCO into ULO, the flame temperatures can be decreased. The premixed burner produced 86.67% and 71.23% less CO and HC emissions, respectively, than the diffusion burner, in contrast, the premixed burner formed 26.31% and 54.7% higher CO 2 and NO x emissions, respectively, than the diffusion burner.